Representation of Gender in Young Adult Fiction: A Feminist Discourse Analysis of Suzanne Collins’ The Hunger Games - Dr. Mamona Yasmin Khan; Sadaf Khan (Indus Journal of Social Sciences, 2025)
This study uses feminist critical discourse analysis (FCDA) to examine how gender roles are constructed and negotiated in Suzanne Collins’ 2008 novel The Hunger Games. Adolescent views are shaped by Young Adult (YA) literature, and Collins’ dystopian story, with a strong female lead named Katniss Everdeen, makes a strong argument for analyzing gendered power dynamics. While earlier researches have concentrated on the novel’s political and thematic aspects, this study fills a crucial void by examining the discursive ways in which language, narrative devices, and character interactions either question or uphold conventional gender standards. The goal of the study is to identify the various ways that gender beliefs are incorporated and challenged within the text by looking at micro-level discourse elements like dialogue, vocabulary choices, and narrative structure. The study aims to address the construction of gender roles, the expression or undermining of feminist ideas, and the protagonist’s maneuvering within patriarchal frameworks. In conclusion, this work highlights how YA fiction shapes young readers’ perceptions of gender identity, power, and social standards in addition to adding to feminist literary critique.